ANALISIS MOTIVASI BELAJAR PESERTA DIDIK PADA KELAS IX SMP NEGERI 24 PONTIANAK - Dani Ariyadi; Purwanti Purwanti; Luhur Wicaksono (Universitas Tanjungpura, 2019)
AbstractThis research is about The Motivation in Learning of Pontianak Junior High School Number 24, Ninth Class Students. The matters of this research are, how are the characterictics of students who have motivation in learning, how are the intrinsic motivation in learning of students, how are the extrinsic motivation in learning of students The purposes of this research are to know about the characterictics of students who have motivation in learning at school, the intrinsic motivation in learning of students at school, the extrinsic motivation in learning of students at school. The method of this research is descriptive method, the type of this research is survey research. The samples of this research are 48 students, this research uses a quantitative approach and indirect communication, and data collection is questionnaire The results of this research show that the motivation in learning are “very high” with a percentage of 85 %. The characterictics of students who have motivation in learning are “very high” with a percentage of 94 %. The intrinsic motivation in learning of students are “very high” with a percentage of 82 %. The extrinsic motivation in learning of students are also “very high” with a percentage of 94 %.Keywords: Description, Motivation in Learning